1465Adverse cardiovascular events after cancer in Queensland, Australia. (2nd September 2021) - Diaz, Abbey; Cunningham, Joan; Lindsay, Daniel; Callander, Emily; Sverdlov, Aaron; Shaw, Joanne; Griffiths, Kalinda; Garvey, Gail
Abstract: Background: Cancer survivors are at increased risk of cardiovascular (CV) disease, partially due to cardiotoxic anti-cancer therapies and elevated CV risk factor exposure. We describe the prevalence of adverse CV events in Queensland cancer survivors. Methods: The Queensland Cancer Registry (QCR) identified all Queensland residents diagnosed with cancer, July 2012-June 2015. Individuals were included at their first tumour and excluded if diagnosis basis was unknown/post-mortem. The QCR, containing demographic and clinical information, was linked to Queensland Hospital Admitted Patient Data Collection records to evaluate pre-cancer CV comorbidity and post-cancer adverse CV events. All individuals had three years follow-up time. Results: 79, 377 people with cancer were included. Median diagnosis age was 67 years (IQR 56-76), 44.6% were women, 5.3% had CV comorbidity and the most common cancers were prostate (19.8%), breast (17.3%), and colorectal (15.2%). 10.7% of people had an adverse CV event during follow-up; median time to first event was 362 days (IQR 124-706). Adverse CV events were most common in those aged >35 years vs ≤ 35 (11.0% vs 2%), men vs women (12.3% vs 8.7%), those with vs without CV comorbidity (29.7% vs 9.6%), and in bladder (14.7%), lung (13.1%), or colorectal (12.4%) cancer patients. Conclusions: One in ten Queensland cancer patients are hospitalised for adverse CV events in the first three years after cancer diagnosis, associated with CV comorbidity, older age, male sex, and cancer type. Key messages: There is urgent need for strategies to identify and deliver optimal care to cancer patients at high CV risk.